Serum zinc concentrations and indices of inflammatory response and serum IgA in children with infectious diarrhea - V. V. Pechuhina; O. V. Usachova (Patologìâ)
Аim. The objective of this study was to give a comparative characteristic of laboratory manifestations for the inflammatory process and the level of serum IgA in infectious diarrhea in young children, depending on serum zinc concentrations.